Density, abundance and group size of river dolphins (Inia geoffrensis and Sotalia fluviatilis) in Central Amazonia, Brazil - PAVANATO, H.J.; Salazar, C.Gomez; Lima, D.; Paschoalini, M.; Ristau , N.; Marmontel, M. (J. Cetacean Res. Manage., 2019)
Given the difficulties and costs often associated with surveying cetaceans, enlisting members of the public to collect data offers a promising alternative approach. Comparison of cetacean ‘participatory science’ (also known as ‘citizen science’) data with data collected during traditional scientific studies helps reveal the strengths and weaknesses of a participatory science approach. With a large number of vessel operators on the water throughout the year, including dolphin-oriented tour boats, the Hawaiian Islands offer an ideal study site to employ such a dual-method comparison. The study aimed to enhance understanding of nearshore dolphin distributions relative to bathymetry. Operators of tour and fishing vessels within the shallow Maui Nui basin of the Hawaiian Islands were recruited to report delphinid sightings. Researchers conducted standard dolphin surveys within the same region. The participatory science approach was successful in generating a large sample size of sightings from five different species. Findings here demonstrate the potential value of participatory science and of using a multimethod approach to infer odontocete distribution trends relative to bathymetry in areas where both methods are feasible. Important refinements for future projects are highlighted.